Implementasi Benchmarking dalam Bentuk Kegiatan Studi Banding Perpustakaan Universitas Muhammadiyah Bengkulu - Ekma Nada Putri; Asep Asep; Lailatus Sa’diyah (Penelitian dan Pengembangan Ilmu, 2024)
Benchmarking is a standard or benchmark used to compare an organization with other organizations operating in a similar field. This certainly helps organizations such as PT Libraries to be able to make comparisons with other superior PT Libraries as a benchmark. This research aims to determine the application of benchmarking in the form of comparative study activities at the Muhammadiyah University of Bengkulu Library. This research uses a qualitative method with a descriptive approach obtained by interviews, observation and documentation. Determining informants was carried out using the snowball sampling method with three informants, namely librarians. Researchers use theory by Peter Brophy and Kate Coulling which consists of five indicators, namely plan, analyze the process, design the study and gather information, compare performance, design and implement improve activity. The research results show that the implementation of benchmarking in the form of comparative study activities carried out by the Muhammadiyah Bengkulu University library for library accreditation and improving the quality of library management was carried out well, even though it was constrained by the funds owned by the library and the presence of Covid-19. This is demonstrated by the initial steps in planning the implementation of benchmarking activities, direct visits to university libraries which are used as benchmarks, and the implementation of all the findings obtained which are adjusted to the existing conditions in the Muhammadiyah University of Bengkulu library.